Caralluma fimbriata extract activity involves the 5‐HT2c receptor in PWS Snord116 deletion mouse model. Issue 12 (23rd October 2018) - Griggs, Joanne L.; Mathai, Michael L.; Sinnayah, Puspha
Abstract: Introduction: In Prader–Willi syndrome (PWS), nonprotein coding small nucleolar (sno) RNAs are involved in the paternally deleted region of chromosome 15q11.2‐q13, which is believed to cause the hyperphagic phenotype of PWS. Central to this is SnoRNA116 . The supplement Caralluma fimbriata extract (CFE) has been shown to decrease appetite behavior in some individuals with PWS. We therefore investigated the mechanism underpinning the effect of CFE on food intake in the Snord116del mouse. Experiments utilized appetite stimulants which included a 5‐hydroxytryptamine (5‐HT) 2c receptor antagonist (SB242084), as the 5‐HT2cR is implicated in central signaling of satiety. Methods: After 9‐week chronic CFE treatment (33 mg or 100 mg kg −1 day −1 ) or placebo, the 14‐week‐old Snord116del (SNO) and wild‐type mice ( n = 72) were rotated through intraperitoneal injections of (a) isotonic saline; (b) 400 mg/kg of 2‐deoxyglucose (2DG) (glucose deprivation); (c) 100 mglkg beta‐mercaptoacetate (MA), fatty acid signaling; and (d) SB242084 (a selective 5HT2cR antagonist), with 5 days between reagents. Assessments of food intake were from baseline to 4 hr, followed by immunohistochemistry of neural activity utilizing c‐Fos, neuropeptide Y, and alpha‐melanocyte‐stimulating hormone within hypothalamic appetite pathways. Results: Caralluma fimbriata extract administration decreased food intake more strongly in the SNO100CFE group with significantly stimulated food intake demonstrated during coadministration with SB242084. Though stimulatory deprivation was expected to stimulate food intake, 2DG and MA resulted in lower intake in the snord116del mice compared to the WT animals ( p = <0.001). Immunohistochemical mapping of hypothalamic neural activity was consistent with the behavioral studies. Conclusions: This study identifies a role for the 5‐HT2cR in CFE‐induced appetite suppression and significant stimulatory feeding disruptions in the snord116del mouse model. Abstract : We utilized the Prader–Willi syndrome (PWS), Snord116 deletion mouse model, and stimulatory feeding to identify the mechanistic underpinnings of suppression of food intake, due to administration of the Indian cactus supplement "Caralluma fimbriata extract" (CFE). The PWS strain demonstrated unusual appetite signaling during glucose deprivation compared to the wild‐type strain and the experimental protocol ultimately identified the role of the 5‐HT2c receptor in CFE appetite attenuation.